2017
DOI: 10.1017/s1355617717000820
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cognitive Performance and Measures of Neurodegeneration among Hispanic and White Non-Hispanic Individuals with Normal Cognition, Mild Cognitive Impairment, and Dementia

Abstract: Objectives: The aim of this study was to determine the presence and severity of potential cultural and language bias in widely used cognitive and other assessment instruments, using structural MRI measures of neurodegeneration as biomarkers of disease stage and severity. Methods: Hispanic (n = 75) and White non-Hispanic (WNH) (n = 90) subjects were classified as cognitively normal (CN), amnestic mild cognitive impairment (aMCI) and mild dementia. Performance on the culture-fair and educationally fair Fuld Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Among the 16 studies that examined neurodegeneration, 2 measured NfL ( Howell et al, 2017 ; Rajan et al, 2020 ), 4 measured total brain volume ( Minagar et al, 2000 ; Brickman et al, 2008 ; DeCarli et al, 2008 ; Aggarwal et al, 2010 ), 8 measured hippocampal and entorhinal volumes ( DeCarli et al, 2008 ; Zahodne et al, 2015 ; Howell et al, 2017 ; Burke et al, 2018 ; Duara et al, 2019 ; Garrett et al, 2019 ; Morris et al, 2019 ; Arruda et al, 2020 ), 4 measured cortical thickness ( Zahodne et al, 2015 ; McDonough, 2017 ; Rizvi et al, 2018 ; Arruda et al, 2020 ), and 4 measured lateral ventricle size ( Minagar et al, 2000 ; Shadlen et al, 2006 ; Brickman et al, 2008 ; Burke et al, 2018 ). Participants in these studies ranged from cognitively normal, MCI, and AD and were recruited from both ADRC and community settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 16 studies that examined neurodegeneration, 2 measured NfL ( Howell et al, 2017 ; Rajan et al, 2020 ), 4 measured total brain volume ( Minagar et al, 2000 ; Brickman et al, 2008 ; DeCarli et al, 2008 ; Aggarwal et al, 2010 ), 8 measured hippocampal and entorhinal volumes ( DeCarli et al, 2008 ; Zahodne et al, 2015 ; Howell et al, 2017 ; Burke et al, 2018 ; Duara et al, 2019 ; Garrett et al, 2019 ; Morris et al, 2019 ; Arruda et al, 2020 ), 4 measured cortical thickness ( Zahodne et al, 2015 ; McDonough, 2017 ; Rizvi et al, 2018 ; Arruda et al, 2020 ), and 4 measured lateral ventricle size ( Minagar et al, 2000 ; Shadlen et al, 2006 ; Brickman et al, 2008 ; Burke et al, 2018 ). Participants in these studies ranged from cognitively normal, MCI, and AD and were recruited from both ADRC and community settings.…”
Section: Resultsmentioning
confidence: 99%
“…This group additionally reported that Hispanic race was associated with 0.12 mm 3 greater hippocampal volume and 0.13 mm 3 greater entorhinal volume independent of age, gender, functional activities questionnaire score, and MoCA score. In another ADRC-based study of 165 participants with normal cognition, MCI, and dementia, Hispanics showed greater hippocampal and entorhinal volumes relative to nHW after adjusting for age, depression, and Geriatric Depression Scale score ( Burke et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of prognostication, different patterns of cognitive performance may predict eventual conversion to dementia in different ethnic/racial groups (Weissberger et al, 2013). As for biomarkers, a pertinent example is that the correspondence between the degree of MTL atrophy in MCI and the magnitude of cognitive dysfunction on testing varies across race/ethnicity despite controlling for various risk factors (DeCarli et al, 2008; Burke et al, 2018; Weissberger et al, 2019). It is reasonable to assume that cultural bias on testing has a similar impact on MCI and dementia in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Atrophy of the medial temporal and parietal lobe is thus common, although not specific, of AD. Volumetric studies of these areas show a 10% volume decrease in patients with mild cognitive impairment (MCI) due to AD (Chan et al, 2003; Frisoni et al, 2009) and a correlation of these volumes with the severity of cognitive impairment (Burke et al, 2018). Consistently, hippocampal atrophy and parietal atrophy are significant predictors of progression from MCI to dementia, most frequently due to AD (DeCarli et al, 2007; Jack et al, 1999; Da et al, 2013; Pyun et al, 2017; Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%